Atomic-scale Investigation of Interface Between Graphene Monolayer and Ge(110) - Park, Sangwoo; Jeong, Taehwan; Kang, Hyunmin; Jung, Seong Jun; Lee, Jae Hyun; Suh, Hwansoo; Whang, Dongmok; Song, Young Jae (Journal of the Korean Physical Society, 2019)
The interface states at the graphene-dielectric substrate are scientifically and industrially important to control the electronic properties for the graphene-based applications. In this report, we present the atomic and electronic structures of graphene on Ge(110), studied by scanning tunneling microscopy and spectroscopy (STM/STS) in an atomic scale. We observed Ge pentamers and ridge structures. The strong electric coupling at the interface and the existence of the Ge pentamers were confirmed by additional peaks at −0.55 V and −0.20 V in the dI/dV spectra. Based on the analysis of the energy gap mappings near the ridges of graphene, extracted from the two-dimensional STS measurements, we could tell the effects of the graphene strain and the interfacial gap distance on the electronic structures of graphene/Ge(110).
Keywords: Ge pentamer; Germanium; Graphene; Interface states; Strain